Pioneers of discovery - Rennert, Richard Scott, 1956- (New York : Chelsea House, 1994)
Short biographies of eight black American pioneers of discovery, including Benjamin Banneker, George Washington Carver, and Lewis Latimer.
Includes bibliographical references and index.
Keywords: African American scientists -- Biography -- Juvenile literature; Discoveries in science -- United States -- History -- Juvenile literature; Scientists; African Americans -- Biography